PENERAPAN METODE FULL COSTING DALAM MENGHITUNG HARGA POKOK PRODUKSI PADA UMKM DI DESA BONTOSUNGGU, BONTOHARU, KEPULAUAN SELAYAR - Ari Utomo Saputra; Ari Ayu; Nurul Alfaina; Bondo Bondo; Viki Wahyudi; Rini Apriani (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the application of the Full Costing method in calculating the cost of goods manufactured (COGM) among MSMEs in Bontosunggu Village, Bontoharu District, Selayar Islands. Most MSMEs still use simple calculation methods that only include raw materials and direct labor, while indirect costs such as electricity, depreciation, transportation, and rent are often ignored. This condition results in selling prices that do not reflect actual costs, leading to thin profit margins and even potential losses. The research employs a descriptive qualitative approach using in-depth interviews, observations, and document triangulation. Informants consist of MSME actors in the food and craft sectors as well as representatives from related government agencies. Data were analyzed thematically using a contingency theory framework to assess the suitability of the Full Costing method with the characteristics of island-based MSMEs. The findings indicate that MSME actors have limited understanding of cost structure and financial recording, while selling prices are determined based on market trends rather than cost calculations. However, there is strong enthusiasm to learn better accounting and record-keeping systems. The application of Full Costing is considered relevant but needs to be simplified to match MSME capacity. The study concludes that a simplified adaptation of the Full Costing method can improve the accuracy of COGM calculation, profitability, and MSME competitiveness in a sustainable manner.